Effective estimation of correct platelet counts in pseudothrombocytopenia using an alternative anticoagulant based on magnesium salt. (29th June 2013) - Schuff‐Werner, Peter; Steiner, Michael; Fenger, Sebastian; Gross, Hans‐Jürgen; Bierlich, Alexa; Dreissiger, Katrin; Mannuß, Steffen; Siegert, Gabriele; Bachem, Maximilian; Kohlschein, Peter
Summary Pseudothrombocytopenia remains a challenge in the haematological laboratory. The pre‐analytical problem that platelets tend to easily aggregate in vitro, giving rise to lower platelet counts, has been known since ethylenediamine‐tetra acetic acid EDTA and automated platelet counting procedures were introduced in the haematological laboratory. Different approaches to avoid the time and temperature dependent in vitro aggregation of platelets in the presence of EDTA were tested, but none of them proved optimal for routine purposes. Patients with unexpectedly low platelet counts or flagged for suspected aggregates, were selected and smears were examined for platelet aggregates. In these cases patients were asked to consent to the drawing of an additional sample of blood anti‐coagulated with a magnesium additive. Magnesium was used in the beginning of the last century as anticoagulant for microscopic platelet counts. Using this approach, we documented 44 patients with pseudothrombocytopenia. In all cases, platelet counts were markedly higher in samples anti‐coagulated with the magnesium containing anticoagulant when compared to EDTA‐anticoagulated blood samples. We conclude that in patients with known or suspected pseudothrombocytopenia the magnesium‐anticoagulant blood samples may be recommended for platelet counting.